Analisis identifikasi kebutuhan fisik yang dominan bagi atlet panahan - Mukholid, Agus; Liskustyowati, Hanik; Sabarini, Sri Santosa; Nugroho, Djoko; Putro, Baskoro Nugroho (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2025)
This study aims to determine the quantitative relationship between physical factors such as height, weight, arm length, length of the span of both arms and hand pull strength on archery performance in archery athletes participating in the Central Java National Sports Week. This study uses a quantitative survey method. The sample involved was 28 athletes of the Central Java National Sports Week (PON) who were selected using a purposive sampling technique. The data collection techniques in this study are tests and measurements. The results showed that there was no significant relationship between height, weight, arm length, length of the span of both arms, and hand-pulling strength with archery results. These physical factors are not the main determinants of archery achievement. The results showed that there was a significant relationship between height, weight, arm length, length of the span of both arms, and hand-pulling strength with archery results. Each variable is marked with an R-value of 0.82. Based on these results, height, weight, arm length, length of the span of both arms and hand pull strength are very important factors in supporting the dominant physical needs of archery athletes. This research has important implications for coaches and athletes, namely that the focus in training should be more directed at developing mental techniques and skills rather than simply relying on or modifying physical factors. Comprehensive skill development and experience enhancement can be a more effective strategy to improve achievement in archery.